A Roadmap to the Brittle Bones of Cystic Fibrosis - Ashwini P. Gore; Soon Ho Kwon; Antine E. Stenbit (Journal of Osteoporosis)
Cystic fibrosis (CF) is an autosomal recessive disorder which despite advances in medical care continues to be a life-limiting and often fatal disease. With increase in life expectancy of the CF population, bone disease has emerged as a common complication. Unlike the osteoporosis seen in postmenopausal population, bone disease in CF begins at a young age and is associated with significant morbidity due to fractures, kyphosis, increased pain, and decreased lung function. The maintenance of bone health is essential for the CF population during their lives to prevent pain and fractures but also as they approach lung transplantation since severe bone disease can lead to exclusion from lung transplantation. Early recognition, prevention, and treatment are key to maintaining optimal bone health in CF patients and often require a multidisciplinary approach. This article will review the pathophysiology, current clinical practice guidelines, and potential future therapies for treating CF-related bone disease.